Praktik Komunikasi Politik Calon Legislatif & Anggota Legislatif Perempuan di Wilayah Jawa Timur Serta Implikasinya bagi Representasi Gender - Suprihatin; Wulandari, Anita Agustina; Sari, Ratna Puspita; Oktarina, Riesta Ayu; Amalia, Dwi Ananda (KOMUNIKATIF : Jurnal Ilmiah Komunikasi, 2025)
ABSTRACT The affirmative action policy mandating a 30% quota for women in legislative candidacy is stipulated in the Indonesian General Election Law (Law No. 7 of 2017). Nevertheless, women’s representation in both national and regional parliaments has yet to reach the intended target. This study aims to explore the underlying reasons for the unmet 30% quota by examining the political communication strategies employed by female legislators in East Java and assessing the extent to which these strategies influence their electability and representation. Using a qualitative–exploratory approach, data were collected through in-depth interviews with female legislative candidates who previously contested but were unsuccessful, as well as with currently serving female legislators. The data were analyzed using the Miles and Huberman interactive model. The findings indicate that the failure to achieve the 30% quota is not due to the absence of effective political communication strategies among female candidates. In fact, the informants employed a range of strategies, including grassroots engagement, the use of social media, and the mobilization of community networks. However, structural barriers within political parties, patriarchal cultural norms, the dominance of male candidates, and internal party hierarchies significantly constrained women’s chances of being elected. Additionally, political capital—particularly access to financial resources and advantageous ballot placement—played a decisive role in electoral outcomes, often outweighing the impact of communication strategies. The study concludes that beyond the need for more targeted political communication strategies tailored to specific constituencies, broader institutional reforms, enhanced public political education (political literacy), and a more equitable party system are essential to strengthening women’s political representation. ABSTRAK Kebijakan afirmasi yang mewajibkan kuota 30% untuk perempuan dalam pencalonan legislatif telah disuratkan dalam Undang-Undang Pemilihan Umum Nomor 7 Tahun 2017. Namun demikian representasi perempuan di parlemen nasional dan regional tetap belum berhasil mencapai target. Penelitian ini bertujuan mengeksplorasi mengapa kuota afirmasi 30% belum terpenuhi, dengan berfokus pada strategi komunikasi politik yang digunakan oleh anggota legislatif perempuan di Jawa Timur, dan sejauh mana strategi tersebut mempengaruhi elektabilitas dan representasi mereka? Dengan pendekatan kualitatif-eksploratif, penelitian ini mengumpulkan data melalui wawancara mendalam pada calon legislatif yang sudah maju namun gagal terpilih dan anggota legislatif perempuan yang saat ini aktif menjabat. Data dianalisis menggunakan model Miles dan Huberman. Temuan menunjukkan bahwa kegagalan mencapai kuota 30% bukan disebabkan oleh kurangnya strategi komunikasi politik yang efektif dari calon perempuan. Faktanya, narasumber menggunakan strategi yang beragam, termasuk keterlibatan akar rumput, pemanfaatan media sosial, dan jaringan komunitas. Namun, hambatan struktural dalam partai politik, norma budaya patriarki, dominasi calon laki-laki, dan hierarki internal partai secara signifikan menghambat peluang perempuan untuk terpilih. Selain itu, modal politik, termasuk akses ke sumber daya keuangan dan nomor urut dalam pemilihan yang menguntungkan, memainkan peran yang menentukan hasil pemilihan—hal ini seringkali melebihi efektivitas komunikasi. Hasil dari penelitian menemukan bahwa adanya kebutuhan strategi komunikasi politik yang lebih tepat, juga kebutuhan akan reformasi institusional, peningkatan pendidikan politik publik (literasi politik), dan sistem partai yang lebih adil untuk mendukung representasi politik perempuan yang lebih baik.